TEC variations during low solar activity period (2005–2007) near the Equatorial Ionospheric Anomaly Crest region in India - Bagiya, Mala S.; Joshi, H.P.; Iyer, K.N.; Aggarwal, Malini; Ravindran, S.; Pathan, B.M. (My University, 2009)
The dual frequency signals from the GPS satellites recorded at Rajkot (22.29° N, 70.74° E, Geographic, 14.03° N Geomagnetic) near the Equatorial ionization anomaly crest in India have been analyzed to study the ionospheric variations in terms of Total Electron Content (TEC) for the low solar activity period from April 2005 to December 2007. In this study, we describe the diurnal and seasonal variations of TEC, solar activity dependence of TEC and effects of a space weather related event, a geomagnetic storm on TEC. The diurnal variation of TEC shows pre-dawn minimum for a short period of time, followed by a steep early morning increase and then reaches maximum value between 14:00 LT and 16:00 LT. The mean diurnal variations during different seasons are brought out. It is found that TEC at Rajkot is at its maximum during Equinoctial months (March, April, September, October), and minimum during the Winter months (November, December, January, February), with intermediate values during Summer months (May, June, July, August), showing a semi annual variation. TEC values have been decreasing since 2005, onwards showing positive correlation with solar activity. TEC variations during the geomagnetic storm commencing 24 August 2005 with Dst=−216 nT are analysed. TEC shows a positive ionospheric storm effect on the first day of the storm and negative ionospheric storm effect on the next day. The equatorial Electrojet control on the development of the equatorial anomaly is also demonstrated.
Keywords: GPS satellite; TEC variations; Geomagnetic storms; Equatorial Ionospheric